CITRA PEREMPUAN DALAM HAIKU SUGITA HISAJO Rahajeng Nastya Sekarhayu Mahasiswa Pascasarjana Universitas Negeri Surabaya Email: ajengnastya@gmail.com (Lentera, Jurnal Studi Perempuan, 2014)
Abstract:  A  woman  is  pictured  as  a  person  who  has  tenderness  and  tenacious thought.  As  a  mother,  Japanese  woman  believe  that  she  must  pursues  a  good education, improves her knowledge, and develops her artistic inclinations in order to run her role well. Japanese women are proud to their role as a mother. They take care and teach all of the lessons to their children.  Haiku written by Sugita Hisajo portrays a model of woman as a mother who is kind, intelligent, educate, and willing to  sacrifice  for  the  family  behalf.  Japanese  women  also  play  important role  in  the society. They are smart and have bright views of ideas and knowledge which enable them to take a part in the cultural and political domain. Keywords: mother, smart, educate, willing to sacrifice.